How High is North Korea's Real Employment and Income? - Suk Lee (Korea Development Institute (KDI), 2016)
According to North Korea's 2008 census, about 88% of the population aged 20-59 are officially employed in socialist sectors. However, the actual share of the employed population who can afford a decent living is estimated at 31%-62%. As for North Korea's PPP-based per capita income-calculated using energy usage patterns-it is well in the range of the Bank of Korea's estimates on the North's per capita GNI for 2008, at 948-1,361. On the contrary, Pyongyang has marked the official share of the employed population aged 20-59 at 85% and per capital income at a maximum of 2,715, implying that the capital is more affluent than the rest of the country. - Drawing on the data from the 2008 North Korea Census directly conducted on North Korean people, this study seeks certain implications on the real employment (unemployment) rate in official socialist sectors and the real income level. - Officially, the share of those employed in socialist economic sectors is marked at 88% for those aged 20-59 and 97% for men aged 30-59. - According to official records, North Korea exhibits total employment, meaning all able-bodied and minded North Koreans are employed. - The 2008 census however shows that a large number of North Koreans are regularly engaged in household economic activities such as food production for selfconsumption. - It is doubtful that those engaged in household economic activity actually work in socialist sectors, because the socialist system provides people with food and other consumables and extra economic activities are unnecessary. - Based on these findings, this study compares North Korea's official data on the employed population with the population engaged in household economic activity in order to estimate the real employment or unemployment rates in North Korea's official socialist sectors. - The results show that while the official share of the employed population aged 20-59 is 88%, the share of the real employed population is a minimum of 31% and maximum of 62%. - Pyongyang is the exception as the real employment rate is well in the range of the official rate (85%), at 61-85%. - According to the 2008 census, North Korean's income and consumption are at a very low level. - Energy usage patterns are closely related to income in underdeveloped countries. And the high use of firewood (50%) implies that conditions are extremely primitive. - This study applied North Korea's use of energy sources to estimate the income level. - The results show that, as of 2008, North Korea's PPPbased per capita GDP is estimated to be a minimum of 948 and maximum of 1,361. - However, Pyongyang's per capita GDP is a minimum of 2,658 and maximum of 2,715, much higher than the rest. - These estimates of North Korea's real income are found to be very similar to the Bank of Korea's estimates of North Korea's per capita GNI (in won terms). - However, Pyongyang's real income is estimated to be far above the Bank of Korea's estimate of North Korea's per capital GNI.
Keywords: 330